Impact of Lean Utilization on Operational Performance: A Study of Sri Lankan Textile and Apparel Industry - Gunarathne, G.C.I.; Kumarasiri, W.D.C.K.T. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2017)
The increasingly competitive local and international market for the Textile and Apparel industry has forced the manufacturers to adopt practices that lead to cost reductions and improve Operational Performance (OP). According to Gamage et al. (2010) lean had been initiated to fulfill this requirement. Yet it was crucial to be aware whether Lean Practices would essentially have a positive impact on OP. This research was therefore conducted to identify the relationship between Lean and OP and the impact Lean utilization creates on the OP levels. The objectives also covered the identification of issues that hinder the ability to derive the expected benefits and suggesting how Lean could be used effectively to attain the expected OP levels. A survey questionnaire was used to gather data from Textile and Apparel factories that met the criteria of possessing Lean manufacturing as the standard of operation for more than a period of one year, to ensure adequate time to gain results on an impact on the OP measurement criteria identified in the model. This was studied in a sample of thirty medium to large scale factories registered in the Board of Investments. Data were specifically gathered on Lean utilization under three constructs, Just in Time (JIT), Waste Elimination (WE) and Flow Management (FM) extracted from literature. OP was measured through 12 Key Performance Indicators identified from industry. Descriptive Statistics, Multiple Regression Analysis and Correlation Analysis were employed to analyze the data. Results indicated that there is a positive relationship between Lean Utilization and OP in the Textile and Apparel industry. WE techniques utilized in the industry had a highly significant relationship with OP compared to JIT and FM. Also it was evident that lack of awareness of the human factor, lesser number of studies and consultancy expenses has hindered their ability to gain expected outcomes. The study encourages WE techniques such as elimination of bottlenecks and would support the management in long term decision making.
Keywords: Key Performance Indicators, Lean Practices, Operational Performance, Textile and Apparel Industry